Validation and Reliability of Polish Version of the Reflux Symptoms Index and Reflux Finding Score - Włodarczyk, Elżbieta; Jetka, Tomasz; Miaśkiewicz, Beata; Skarzynski, Piotr Henryk; Skarzynski, Henryk (Healthcare (Basel), 2022)
(1) Background: To confirm the credibility, consistency, and replicability of the Polish versions of the Reflux Symptoms Index (PL-RSI) and the Reflux Finding Score (PL-RFS). (2) Methods: The translation followed the WHO recommendations. The study group included 100 volunteers (age 15–87) with hoarseness and pharyngolaryngeal complaints. The control group comprised 55 healthy volunteers (age 20–75). Study participants completed the PL-RSI; then, two independent otolaryngologists completed the PL-RFS based on pharyngeal videostroboscopy. Questionnaires were repeated after 7 days, with no treatment before the second round. Additionally, patients underwent 24 h pH-metry. The control group had a single round of questionnaires followed by pH-metry. (3) Results: The PL-RSI is consistent, reliable (Cronbach’s alpha 0.77–0.83; test–retest reliability 0.83), and significantly correlated with other patient-filled tools (p < 0.001). The PL-RFS intra-rater reliability is 0.84–0.91, and inter-rater is 0.88. Both questionnaires strongly correlate with pH-metry (PL-RSI upright Ryan Score 0.35, PL-RFS—0.60). Both clearly distinguish (i) healthy from persons with voice disorders, but without acid LPR (p < 0.0001), and (ii) within patient group between subjects with and without acid LPR (p = 0.0002). (4) Conclusions: The PL-RSI and PL-RFS are reliable and can be recommended to Polish-speaking otolaryngologists. Our findings confirm the role of country-specific factors in RSI results and that practitioners should always use a proper control group.